(untitled) (Bioscience Journal, 2019)
We aimed to evaluate the effects of different irrigation depths with saline water on growth, yield, water-use efficiency, and fruit quality of ‘Pérola’ pineapple plant grown in the semi-arid of Bahia state. The experiment was carried out in a randomized block design with five treatments which represented the irrigation depths: 100% of crop evapotranspiration (ETc) with irrigation water of 0.75 dS m-1 in electrical conductivity (ECiw); and 50, 75,100, and 125% of ETc with water of 3.6 dS m-1 in ECiw. Pineapples were grown under field conditions watered by drip irrigation in which pressure compensating emitters had 8 L h-1 flow rate. We observed that the irrigation depth 100% of ETc with water of 0.75 and 3.6 dS m-1 in ECiw provides higher pineapple yields under the semi-arid conditions of this study, and the chemical quality of the fruits are up to commercial standards, except when applying 125% of ETc with water of 3.6 dS m-1 in ECiw.